"Taking action for the Reef?"–Australians do not connect Reef conservation with individual climate‐related actions. Issue 2 (10th September 2020) - Dean, Angela J.; Gulliver, Robyn E.; Wilson, Kerrie A.
Abstract: Climate change is the most significant threat to the Great Barrier Reef (GBR). While Australians express appreciation and concern for the GBR, it is not clear whether they connect climate‐related action with reef conservation. An online survey of 4, 285 Australians asked "…what types of actions could people like you do that would be helpful for the GBR?" Only 4.1% mentioned a specific action related to mitigating climate change; another 3.8% mentioned climate change but no specific action. The most common responses related to reducing plastic pollution (25.6%). These findings demonstrate that most Australians have poor capacity to identify individual climate‐related actions as helpful for reef protection, and that generic calls to action—such as "protect the reef"—are unlikely to elicit climate‐related actions. As such, reef conservation initiatives must explicitly promote actions—in the home and in society—that reduce emissions and support the transition to a low carbon society.